Design of Customer Satisfaction Application at BCA Kcp Rengasdengklok Using C.45 Algorithm Method - April Lia Hananto; Shofa Sofiah Hilabi; Detrie Noviani (Buana Information Technology and Computer Sciences (BIT and CS), 2022)
Bank BCA always improves service quality by the slogan "Always By Your Side". The assessment consists of 4 attributes (time, accuracy, focus, and satisfaction). Each attribute has a weighted value of 1 (very dissatisfied) to 5 (very satisfied). The assessment is still done manually (using paper), therefore the authors in this study used the C.45 algorithm with 3 tests carried out to produce a classification obtained that the accuracy value reached 88.75% with an AUC value of 0.744 and testing on the application that was made resulted in 0.722. It can be concluded that service assessment at BCA KCP Rengasdengklok belongs to a fairly good classification group because its AUC value is between 0.70-0.80.